Contextual determinants of participation after stroke: a systematic review of quantitative and qualitative studies. Issue 13 (19th June 2021) - Della Vecchia, Claire; Viprey, Marie; Haesebaert, Julie; Termoz, Anne; Giroudon, Caroline; Dima, Alexandra; Rode, Gilles; Préau, Marie; Schott, Anne-Marie
Abstract: Purpose: From a patient's perspective, participation is a major determinant of quality of life. We aimed to review contextual factors, both personal and environmental, potentially associated with post-stroke participation. Methods: PubMed, PsycINFO, and Web of Science were searched for original quantitative and qualitative studies that investigated contextual factors of post-stroke participation, measured participation as the primary outcome, and met inclusion criteria. Results: Socio-demographic determinants were mostly unrelated with participation or showed discordant and inconclusive results. Although less investigated, psychosocial/psychological factors, particularly self-esteem and acceptance, were associated with participation in most studies. Motivation was found in qualitative studies, but discordant in quantitative ones. Environmental factors were even less investigated and mainly in qualitative studies among patients with communication disabilities. Among these, social support and attitude of others appeared to be major determinants of participation as well as physical environment and societal environment (services and polices). Conclusions: Personal factors, particularly psychological and psychosocial factors, were identified as positively associated with post-stroke participation. Environmental factors such as support, relationships, and positive attitudes towards patients were major facilitators of participation as well as physical environment and accessibility to appropriate services. Most of these factors are modifiable and should be addressed to improve patient participation. Implications for Rehabilitation: Psychosocial factors (motivational aspects, acceptance of a new condition, self-esteem) and environmental factors (social support, attitudes towards the patient, physical environment, access to health, social services and policies) were identified as determinants of post-stroke participation. A structured evaluation of determinants of participation may be used in clinical practice to propose appropriate support and then improve patients' recovery Programs to improve patients' psychosocial skills such as self-esteem, acceptance, motivation should be tested and implemented, and policies to develop appropriate services accessibility should be encouraged.